2014
DOI: 10.1089/jmf.2013.0189
|View full text |Cite
|
Sign up to set email alerts
|

High-Rosmarinic Acid Spearmint Tea in the Management of Knee Osteoarthritis Symptoms

Abstract: NCT01380015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…The role of RosA in rheumatoid arthritis was also reported [11][12][13]. Moreover, Connelly et al reported that daily consumption of the RosA improved stiffness and physical disability scores in adults with knee OA [14]. However, the mechanism of RosA in OA is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The role of RosA in rheumatoid arthritis was also reported [11][12][13]. Moreover, Connelly et al reported that daily consumption of the RosA improved stiffness and physical disability scores in adults with knee OA [14]. However, the mechanism of RosA in OA is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…for placebo -Increased extension scores from baseline to day 28 for glucosamine/chondroitin vs. UP1306 (p = 0.018) and placebo vs. UP1306 (p = 0.042) -Distance walked (6MWT) increased within-groups from baseline to all time-points. No significant differences between groups (p = 0.183) -TNFα levels: No significant differences from baseline to 12 weeks between groups (p = 0.786) -Urinary CTX-II levels: Significant difference for UP1306 and placebo after 12-weeks (p = 0.029) -VAS scores-pain reduction (p = 0.0001) -WOMAC -total (p = 0.0102) -WOMAC -pain (p = 0.0293) -WOMAC -stiffness (p = 0.002) -WOMAC -function (p = 0.0152) -Blood MMP-9 levels (p = 0.026) Not Reported [58] -WOMAC -pain decreased from baseline in the treatment group (p = 0.002) -WOMAC -stiffness decreased from baseline in the treatment group (p = 0.004) -WOMAC -physical disability decreased from baseline in the treatment group (p = 0.02) -WOMAC scores on all scales were not significantly different between groups -SF-36 QoL score (bodily pain) increased from 46.6 ± 7.6 (baseline) to 58.1 ± 22.1 (week 16) in the treatment group (p < 0.05) -Six-minute walk test change from baseline was +22.3 m for the treatment group and +0.1 m for the control group with no significant differences within or between groups -Overall, no serious adverse events reported -AEs in treatment group: constipation (n = 3), headache (n = 2), loose bowel movements (n = 1) -AEs in control group: staining of dentures (n = 1), dry mouth (n = 1), itchy skin (n = 1) [133] -Muscle function: isokinetic extension peak torquetime * group interaction (p = 0.03), effect sizes were higher in the treatment group for all domains of muscle function -Knee function: time was a significant factor in the domain of "pain on ascending or descending stairs" (p < 0.01) Kellgren and Lawrence (K-L) grade had a main effect in "pain on walking" (p = 0.04) and "range of motion" (p < 0.…”
Section: Turmeric (Curcuma Domestica) (Curcuma Longa)mentioning
confidence: 96%
“…Data from 46 participants (mean age = 60.7; BMI = 32.9 kg/m 2 ) showed that pain score considerably decreased from week 0 to 16 for the high-rosA group instead of the control group, as well as scores for physical disability and stiffness for both groups. Additionally, increased quality of life (QoL) score on the bodily pain index in the SF-36 was observed at week 16 within the high-rosA group only, as well as a non-significant improvement in the six-minute walking test (6MWT) [133].…”
Section: Spearmint (Mentha Spicata)mentioning
confidence: 99%
“…However, no other measures of disability or quality of life showed significant differences between groups (Connelly et al . ). A tart cherry juice was assessed for efficacy in reducing pain and inflammation in patients with inflammatory OA.…”
Section: Food Interventionsmentioning
confidence: 97%
“…A spearmint tea containing high levels of rosmarinic acid (20 mg/day) in a trial of 46 patients was completed (NCT01380015) and the authors reported a significant decrease in pain over the 16-week period using the WOMAC system. However, no other measures of disability or quality of life showed significant differences between groups (Connelly et al 2014). A tart cherry juice was assessed for efficacy in reducing pain and inflammation in patients with inflammatory OA.…”
Section: Food Interventionsmentioning
confidence: 99%